Smoky skies and polar air: aerosol microphysics across scales - June, Nicole Ann, author; Pierce, Jeffrey R., advisor; Collett, Jeffrey L., Jr., committee member; Kreidenweis, Sonia M., committee member; Jathar, Shantanu H., committee member; Willis, Megan D., committee member (Colorado State University. Libraries, 2025)
Atmospheric aerosol particles are important to understand as they have implications on climate and human health. These particles may be emitted directly or form in the atmosphere through secondary processes. In this dissertation, we focus on two systems of aerosol sources, microphysics, and chemistry: 1) wildfires and 2) the springtime marine Arctic. Biomass Burning Plume Injection Height: The magnitude of biomass burning impacts on air quality and climate are altered by the biomass burning plume injection height (BB-PIH). However, these alterations are not well-understood on a global scale. We present the novel implementation of BB-PIH in global simulations with an atmospheric chemistry model (GEOS-Chem) coupled with detailed TwO-Moment Aerosol Sectional (TOMAS) microphysics (GC-TOMAS). We conduct BB-PIH simulations under three scenarios: 1) all smoke is well-mixed into the boundary layer, and 2) and 3) smoke injection height is based on Global Fire Assimilation System (GFAS) plume heights. Elevating BB-PIH increases the simulated global-mean aerosol optical depth (10%) despite a global-mean decrease (1%) in near-surface PM2.5. Increasing the tropospheric column mass yields enhanced cooling by the global-mean clear-sky biomass burning direct radiative effect. However, increasing BB-PIH places more smoke above clouds in some regions; thus, the all-sky biomass burning direct radiative effect has weaker cooling in these regions as a result of increasing the BB-PIH. Elevating the BB-PIH increases the simulated global-mean cloud condensation nuclei concentrations at low-cloud altitudes, strengthening the global-mean cooling of the biomass burning aerosol indirect effect with a more than doubling over marine areas. Elevating BB-PIH also generally improves model agreement with the satellite-retrieved total and smoke extinction coefficient profiles. Our two-year global simulations with new BB-PIH capability enable understanding of the global-scale impacts of BB-PIH modeling on simulated air-quality and radiative effects, going beyond the current understanding limited to specific biomass burning regions and seasons. Aerosol Aging in Wildfire Smoke: The evolution of organic aerosol (OA) composition and aerosol size distributions within smoke plumes are uncertain due to variability in the rates of OA evaporation/condensation and coagulation within a plume. It remains unclear how the evolution varies across different parts of individual plumes. We use a large eddy simulation model coupled with aerosol-microphysics and radiation models to simulate the Williams Flats fire sampled during the FIREX-AQ field campaign. At aircraft altitude, the model captures observed aerosol changes through 4 hr of aging. The model evolution of primary OA (POA), oxidized POA (OPOA), and secondary OA (SOA) shows that >90% of the SOA formation occurs before the first transect (~40 min of aging). Lidar observations and the model show a significant amount of smoke in the planetary boundary layer (PBL) and free troposphere (FT), with the model having equal amounts of smoke in the PBL and FT. Due to faster initial dilution, PBL concentrations are more than a factor of two lower than the FT concentrations, resulting in slower coagulational growth in the PBL. A 20 K temperature decrease with height in the PBL influences faster POA evaporation near the surface, while net OA evaporation in the FT is driven by continued dilution after the first aircraft transect. Net OA condensation in the PBL after the first transect is the result of areas with higher OH concentration leading to OPOA formation. Our results motivate the need for systematic observations of the vertical gradients of aerosol size and composition within smoke plumes. Springtime Marine Arctic Sulfur Chemistry: Dimethyl sulfide (DMS) and methanethiol (MeSH) are important natural sources of sulfur to the atmosphere and influence the aerosol populations in the marine atmosphere. We use GC-TOMAS and data from the ARTofMELT field campaign to analyze sulfur chemistry in the Fram Strait during May and June 2023. We find that updating the model to include the emission of DMS from regions of partial ice cover improves model-observation agreement of DMS and MeSH by over half-an-order-of-magnitude. Model-observation agreement of MeSH is less than that of DMS suggesting model biases in MeSH emissions and/or lifetime. The model-observation agreement of DMS and MeSH varies depending on the oceanic DMS concentration dataset. The monthly oceanic DMS climatology has the lowest magnitude bias of atmospheric DMS during periods of ocean influence, while the daily oceanic DMS prediction by an artificial neural network has the most consistent bias for atmospheric DMS across the differing source regions. The primary DMS oxidation pathway in the model is OH-addition with 64% of the DMS oxidation occurring through that pathway in the campaign average; however, the model likely underestimates the importance of the BrO oxidation pathway due to biases in halogen sources and chemistry. During fog, the aqueous oxidation of DMS with O3 becomes important. The DMS oxidation product of DMSO is underestimated in the model due to the biases in DMS, wet deposition of DMSO, and biases in oxidants. Our results motivate the need for continued improvement of the representation of the sulfur budget in the marine Arctic. Aerosol Size and Composition in the Springtime Marine Arctic: Aerosol size and composition are key to understanding aerosol radiative effects as they impact aerosol lifetime, scattering and absorption properties, and ability to be cloud condensation nuclei. In this study, we aim to understand GC-TOMAS biases of aerosol size and composition during ARTofMELT. We conduct several sensitivity model simulations to determine the impact of blowing snow emissions, more vigorous wet-removal, a marine source of SOA precursor, and nucleation from organics with sulfuric acid on model-observation agreement. We find that there is likely an Arctic marine source of SOA precursor contributing to the OA mass and accumulation mode number concentrations during the campaign. However, the model has a high bias in OA mass and in the accumulation mode throughout the campaign, indicating the assumed model emission flux of the marine SOA precursor is high. There is limited ammonia in the region of the ship, limiting the new particle formation (NPF) through ternary nucleation. As a result, the simulations suggest the importance of the organics with sulfuric acid nucleation mechanism to explaining the observed NPF events. Lastly, we find that the removal of accumulation mode particles through drizzle in marine Arctic low-level clouds helps to reduce the overestimate of the accumulation mode, but increases the underestimate of the nucleation mode. Overall, despite continued efforts to understand the aerosol population in the Arctic, there remain deficits in the ability of a regional model to accurately represent the size and composition of aerosols.
Keywords: Arctic; organics; aerosols; wildfire; nucleation